Banana Plant Disease Classification Using Hybrid Convolutional Neural Network. (23rd February 2022) - Narayanan, K. Lakshmi; Krishnan, R. Santhana; Robinson, Y. Harold; Julie, E. Golden; Vimal, S.; Saravanan, V.; Kaliappan, M.
Abstract : Banana cultivation is one of the main agricultural elements in India, while the common problem of cultivation is that the crop has been influenced by several diseases, while the pest indications have been needed for discovering the infections initially for avoiding the financial loss to the farmers. This problem will affect the entire banana productivity and directly affects the economy of the country. A hybrid convolution neural network (CNN) enabled banana disease detection, and the classification is proposed to overcome these issues guide the farmers through enabling fertilizers that have to be utilized for avoiding the disease in the initial stages, and the proposed technique shows 99% of accuracy that is compared with the related deep learning techniques.